2013
DOI: 10.1007/s13744-013-0113-9
|View full text |Cite
|
Sign up to set email alerts
|

Scanning Electron Microscopy Studies of the Antennal Sensilla of Metaphycus parasaissetiae Zhang & Huang (Hymenoptera: Encyrtidae)

Abstract: Metaphycus parasaissetiae Zhang & Huang (Hymenoptera: Encyrtidae) is an important adult parasitoid of Parasaissetia nigra Nietner (Hemiptera: Coccoidea). The external morphology of the antennal sensilla of male and female M. parasaissetiae was examined using scanning electron microscopy. The geniculate antennae of male and female M. parasaissetiae were composed of a scape with a basal radicula, a barrel-shaped pedicel, and a long flagellum. Twelve morphologically distinct types of sensilla were identified, inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
60
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(74 citation statements)
references
References 56 publications
13
60
0
1
Order By: Relevance
“…P. striolata had fewer subtypes of sensilla trichodea and more subtypes of sensilla basiconica (Bartlet et al, ; Zhang et al, ). Compared with other insects, we found that the types and topology of the sensilla on the antennae of P. striolata were similar to those found in Coleoptera (Chen et al, ; Hu et al, ; Sun et al, ; Yan et al, ; Zhang et al, ), but are very different from those in other insects such as Lepidoptera and Hymenoptera (Navasero and Elzen, ; Isidoro et al, ; Zhang et al, ; Zhou et al, ). These observations indicate that the sibling species have not only similar morphology but also similar sensillum types and distribution.…”
Section: Discussionsupporting
confidence: 66%
“…P. striolata had fewer subtypes of sensilla trichodea and more subtypes of sensilla basiconica (Bartlet et al, ; Zhang et al, ). Compared with other insects, we found that the types and topology of the sensilla on the antennae of P. striolata were similar to those found in Coleoptera (Chen et al, ; Hu et al, ; Sun et al, ; Yan et al, ; Zhang et al, ), but are very different from those in other insects such as Lepidoptera and Hymenoptera (Navasero and Elzen, ; Isidoro et al, ; Zhang et al, ; Zhou et al, ). These observations indicate that the sibling species have not only similar morphology but also similar sensillum types and distribution.…”
Section: Discussionsupporting
confidence: 66%
“…The trichoid sen silla were the most abundant and occurred in all flageromeres. Gao et al (2007) stated that trichoid sensilla, with similar size and morphology to that identified in this study in B. vulgaris antennae, have a mechanoreceptor function explained by its fitting to the antenna's cuticle, its spatial arrangement, and absence of pores in Transmission Electron Microscopy (TEM) images (Zhou et al, 2013b). These sensilla respond to air currents and vibrations generated by the drumming of the parasitoid's antennae on the plant structure that has been inhabited by the host, aiding the host's natural enemy to determine its location (Zhou et al, 2013b).…”
Section: Discussionsupporting
confidence: 58%
“…Therefore, the low amount of sensilla types observed in B. vulgaris antennae is justifiable because this ectoparasitoid was found naturally parasitizing only A. grandis, the cotton boll weevil (Toscano & Car valho, 2000b), and P. gossypiella, the pink caterpillar larvae (Toscano & Carvalho, 2000a). Moreover, according to Zhou et al (2013b), male parasitoid species usually present higher number of sensilla than females because their antennae are adapted to detect sexual pheromones released by females; females use their antennae to de tect volatiles from plants attacked by their herbivorous hosts. Because the objective of this study was to describe the sensory components of B. vulgaris and associate them with the species' success for parasitism, only female antennae were analyzed.…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, Ooencyrtus phongi Trjapitzin, Myartseva & Kostjukov, 1977 (Hymenoptera: Encyrtidae), Metaphycus parasaissetiae Zhang and Huang, 2007 (Hymenoptera: Encyrtidae), Trichogramma dendrolimi Matsumura, 1926 andT. australicum Girault, 1912 (Hymenoptera: Trichogrammatidae) have a single club segment in males, which is separated into flagellomeres in females (Amornsak, Cribb & Gordh, 1998;Xi et al, 2011;Zhang et al, 2012;Zhou et al, 2013b). In the case of M. caribea, both sexes have a fused club, which is uncommon.…”
Section: Discussion Antennal Size and Gross Morphologymentioning
confidence: 99%
“…It is common for chalcidoid wasp males to have 1-3 types of sensilla fewer than females (Barlin, Vinson & Piper, 1981;Amornsak, Cribb & Gordh, 1998;Van Baaren et al, 1999;Xi et al, 2011;Zhang et al, 2012;Zhou et al, 2013b;Namikawa & Amornsak, 2016), although in several cases the same number of types was reported for both sexes (Onagbola & Fadamiro, 2008;Jun et al, 2013). Likely, the additional types of sensilla found in females are required for the biological tasks exclusive for that sex, e.g.…”
Section: Morphological Types Of Antennal Sensillamentioning
confidence: 98%